Optimalisasi Pengendalian Persediaan pada UMKM Aju Kopitiam Melalui Pendekatan EOQ dan Reorder Point: Strategi Efisiensi Operasional dalam Konteks Pengabdian Masyarakat - Hery Haryanto; Santi (Indo Publishing, 2025)
Aju Kopitiam, a food and beverage MSME, still faces problems in controlling raw material inventory due to manual recording and ordering based on estimates. This situation causes excess or shortage of stock, which leads to increased operating costs and disrupts service. The objective of this community service project is to optimize raw material inventory control by implementing the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods. These methods are implemented through analysis of the partner's situation and problems, data collection through observation and interviews, and quantitative data processing for EOQ and ROP calculations. Furthermore, these calculation results are entered into a broader resource-based inventory management system. The results of the study show that the application of the EOQ and ROP methods can help partners determine the ideal quantity and timing of reorders. This makes raw material inventory more controllable, reduces the risk of excess and shortage of stock, and improves the operational efficiency of MSMEs.